TINGKAT PENDAPATAN PEDAGANG MAKANAN KHAS DANAU MANINJAU DI NAGARI MANINJAU DAN BAYUR - Syukrina, Aulia (JURNAL BUANA, 2026)
The aim of this study is to analyze the income levels of food vendors selling typical Maninjau Lake dishes in Nagari Maninjau and Bayur, as well as the factors influencing their income. This research is descriptive-quantitative, with a population consisting of all food vendors in the two nagaris, using the Total Sampling method. The data covers vendors' income levels, business capital, sources of capital, business experience, operating hours, and business duration. The results indicate that the highest income is derived from the sale of "Pensi" (fish), while "Nila Salai" (smoked tilapia) generates the lowest income. The most influential factors on income are capital, sources of capital, and business experience. The majority of business capital comes from personal savings, while longer business duration provides advantages such as a broader customer network and a good reputation. This study highlights the importance of local policy support in sustaining the economic viability of food vendors, particularly through entrepreneurship training and culinary tourism promotion.